Oxide semiconductor nanowires and si-based nanomaterials : synthesis and properties - Zhang, Zhou (2011)
The main objective of this dissertation is to extend the understanding of nanofabrication mechanisms and achieve controlled synthesis of functional nanomaterials with predesigned morphologies and properties, which are potential candidates of building blocks for future nanodevices and nanomachines. Thanks to the fast growth of material characterization techniques, especially the developments of non-optical microscopes (such as scanning tunneling microscope, atomic force microscope, electron microscope, etc.), lots of interests have been drawn to nanomaterials in the recent decades. Aside from their intrinsic advantage of small size which warrants non-replaceable applications in specific areas, nanomaterials also possess many outstanding physical and chemical properties compare to the bulk and film counterparts. However, industrial applications of nanomaterials are still limited due to the lack of knowledge in nanoscale dynamics, nanofabrication techniques, etc. Thus systematic studies are motivated to achieve reliable methods of nanomaterial synthesis with high quality and prominent properties. In this dissertation, we studied the fabrication of several metal oxide and silicide nanomaterials (in particular, ZnO, SnO2, MgO, Cu3Si, and Mg2SiO4), using a simple method of vapor transport.